Activity budgets in different habitats of a species of conservation concern in Ireland, the Light-bellied Brent Goose Branta bernicla hrota - PÃ©rez Tadeo, MarÃa; Gammell, Martin (Wildfowl, 2018)
Activity budgets of Light-bellied Brent Geese Branta bernicla hrota wintering in Ireland were compared at different sites and associated habitats along the coast of inner Galway Bay. Hourly energy expenditure (HEE) by birds feeding on traditional, natural wetlands was compared to their HEE when on managed grasslands. Their flying and vigilance behaviours, and flock size when on these different habitats, were also assessed. Brent Goose HEE did not vary significantly between general areas or specific habitats, but vigilance behaviour was more frequent when the birds were on managed grassland. Flock size was larger in relatively undisturbed natural wetlands. The effects were limited, however, suggesting that there was little cost to Brent Geese from feeding in grassland versus wetland habitats.